2020
DOI: 10.3389/fonc.2020.01302
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Immune-Related Genes in the Tumor Microenvironment of Bladder Cancer

Abstract: The tumor microenvironment (TME) is a complex system that plays an important role in tumor development and progression, but the current knowledge about its effect on bladder cancer (BC) is scarce. In this study, we performed a comprehensive analysis of the relationship between the TME and gene expression profiles to identify prognostic biomarkers for BC. The ESTIMATE algorithm was used to calculate immune and stromal scores of BC patients who were obtained from the Gene Expression Omnibus database. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 48 publications
4
33
0
Order By: Relevance
“…Furthermore, the correlation between COL1A1 and the B7-CD28 ligand-receptor family was analyzed based on TCGA database, indicating there was a close positive correlation between COL1A1 and CD276, which was consistent with the prognostic value of COL1A1. Previous study shown that COL1A1 was correlated positively with the tumor infiltration levels of CD4+ T cells and macrophages in Bladder Cancer (Li et al, 2020). CD276, expressed in multiple tumor lines, tumor-infiltrating dendritic cells, and macrophages, can inhibit T-cell activation and autoimmunity (Son, Kwon & Cho, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the correlation between COL1A1 and the B7-CD28 ligand-receptor family was analyzed based on TCGA database, indicating there was a close positive correlation between COL1A1 and CD276, which was consistent with the prognostic value of COL1A1. Previous study shown that COL1A1 was correlated positively with the tumor infiltration levels of CD4+ T cells and macrophages in Bladder Cancer (Li et al, 2020). CD276, expressed in multiple tumor lines, tumor-infiltrating dendritic cells, and macrophages, can inhibit T-cell activation and autoimmunity (Son, Kwon & Cho, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…Targeted inhibition of ANXA1 can reduce the function of Tregs and shrink breast tumors [ 46 ]. COL4A2 expression is positively correlated with the presence of macrophage and dendritic cell infiltration in cervical-cell cancer, while COL1A1 is positively correlated with tumor infiltration levels of macrophages and CD4 + T cells in bladder cancer [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between numerous components of TME may result in different tumor growth patterns and prognosis, but the precise mechanisms remain to be elucidated and thoroughly investigated. Li et al recently found that three immune-related genes ( COL1A1 , COMP , and SERPINE2 ) are significantly correlated in both TME and tumor prognosis, thus revealing the possible effects and pathways of microenvironment on tumor prognosis ( 22 ). Huo et al analyzed the scores of 22 immune cells in tumor tissues using gene expression data from 816 HNSCC patients and developed a TME score-based prognostic risk model accordingly.…”
Section: Discussionmentioning
confidence: 99%